Training on the Utilization of Cloud Storage and Data Encryption in the Archiving of Authentic Deeds by Notaries on Sebesi Island, South Lampung - Rendy Renaldy; Andriansyah Kartadinata; Eko Aziz Apriadi (CV. Tripe Konsultan, 2025)
This community service activity focuses on improving the digital literacy of notaries and prospective notaries in Pulau Sebesi, South Lampung, regarding the secure archiving of authentic deeds through cloud storage and data encryption. The purpose of this program is to enhance understanding of legal and technological aspects of digital archiving in accordance with the Notary Law and the Electronic Information and Transactions Law. The method used was a participatory-collaborative approach involving legal socialization, technical training, and direct mentoring. Participants were introduced to encryption practices and the use of cloud platforms for secure document management. The results showed an increase in participants’ knowledge and skills in applying digital security principles to notarial archives, as well as the formation of a digital notary group committed to continuing technological adaptation for legal documentation in remote island areas.